ANALISIS FRAMING KEBIJAKAN PEMERINTAH TERKAIT KARTU PRAKERJA SEBAGAI DAMPAK COVID-19 (Analisis pada Kompas.com dan Tribunnews.com) - Walimatul Istiana; yenrizal yenrizal; Eraskaita Ginting (Program Studi Ilmu Komunikasi Fakultas Ilmu Sosial dan Politik Universitas Islam Negeri Raden Fatah Palembang, 2022)
The Covid-19 case in Indonesia has caused many people to be laid off. President Joko Widodo launched the Pre-Employment Card Program as a step to help the unemployed and the people affected by Covid-19 which has caught the public's attention. The online media Kompas.com and Tribunnes.com are some of the media that report the case of the Pre-Employment Card program with the characteristics of their respective media, and do not escape their ideology. Both online media have many readers and are in the top 4 of the 10 most accessed news websites in Indonesia on the world website Alexa.com. The purpose of this study was to find out how the syntactic, script, thematic and rhetorical structure of Zhondang Pan and Kosicki's framing analysis of the news frame of government policies related to the Pre-Employment Card as the impact of Covid-19 on the online media Kompas.com and Tribunnews.com. The method used in this research is a qualitative descriptive approach. The technique of collecting data with documentation is through written archives from the media Kompas.com and Tribunnews.com. The researcher uses Zhondang Pan and Kosicki's theory of framing analysis with syntactic, script, thematic and rhetorical devices. Based on the results of the analysis, Kompas.com clearly shows that this media is more directed towards parties that are opposite or contra with the government, in other words, they do not agree with the Pre-Employment Card program. Meanwhile, Tribunnews.com implicitly gives a point of view of siding with the government or supporting the Pre-Employment Card program.